Globalisation and Indonesia’s demand for dual citizenship: problems and alternatives - Antikowati, Antikowati; Ulum, Muhammad Bahrul; Soetijono, Iwan Rachmad; Nugraha, Reyka Widia (Faculty of Law, University of Muhammadiyah Malang, 2023)
This paper aims to discuss Indonesia's current legal framework of citizenship following its more pervasive demand to adopt dual citizenship. It argues that several issues regarding citizenship law in Indonesia have been relatively problematic, mainly related to the change of citizenship status contentiously experienced by Arcandra Tahar, Gloria Natapraja, and Djoko Tjandra to the increasing demand for dual citizenship. On the other hand, in this context, Indonesia's diasporas have voiced this interest in legal reform, resulting in more flexible opportunities and supporting transboundary businesses, as they have encountered some challenges due to restricted citizenship regulations. Using legal research, this study showed that citizenship had become a strategic issue with far-reaching implications. While Indonesia adopts a limited scale of dual citizenship and the vigour for dual citizenship has increased, the flexibility over dual citizenship requires further study of national security and citizens' loyalty to Indonesia. This paper suggested in adopting India’s OCI model for Indonesia’s citizenship policies as ample opportunities for this country’s citizens with foreign status to continue enjoying and accessing their rights in Indonesia, except in the political field. This measure subsequently would be a step forward to adapt citizenship regulations to globalisation while still paying attention to the nationalism concern.